The synthesis and properties of asymmetric organic-inorganic hybrid polyoxometalates - Hampson, Elizabeth (2021)
The development of accessible synthetic procedures in the preparation of multifunctional hybrid materials which allow fine control in the tuning of their structure and properties is an ongoing challenge. Access to asymmetrically organofunctionalised hybrid polyoxometalates (POMs) could lead to new molecular materials with multiple or modular functionality which can be tailored towards highly specific or advanced applications. Herein, an effective design strategy to the preparation of new asymmetric bi-functionalised hybrid polyoxometalates is presented and the characterisation of the structures and properties of the new multifunctional hybrid compounds is discussed.